A framework for understanding the path to achieve high resilience of maritime supply chain - Xiuqian Chen; Liangyong Chu; Mengyao Wang; Qion Chen (Scientific Reports)
Abstract In recent years, a significant rise in international sudden risk events has resulted in impacts and disruptions to maritime supply chains (MSC). The resilience of maritime supply chains has garnered attention from the academic, industrial, and government sectors. The paper proposes a methodological framework based on the structural equation model (SEM), Necessary Condition Analysis (NCA), fuzzy set qualitative comparative analysis (fsQCA), and utilizes questionnaire data from the maritime industry in China to evaluate the resilience in MSC. The computational results indicate that: (1) The high resilience of MSC is the result of the synergistic interaction among multiple factors, and these factors boost MSC resilience through diverse paths; (2) There are four pathways for high MSC resilience: the ‘collaboration + carbon reduction + digitization’ path, the ‘early warning + collaboration’ path, the ‘agility + early warning’ path, and the ‘carbon reduction’ path; (3) Digitization level can play a catalytic role in increasing the resilience of MSC by helping other factors. This paper reveals the multiple routes to enhance the resilience of MSC, which can instruct MSC members to choose the correct resilience management strategies based on their existing resources and situations and can help both practitioners and researchers to understand in more detail of the various dimensions and nuances of resilience in the context of MSC.